Effect of atorvastatin on skeletal muscles of patients with knee osteoarthritis: Post-hoc analysis of a randomised controlled trial - Lim, Yuan Z.; Cicuttini, Flavia M.; Wluka, Anita E.; Jones, Graeme; Hill, Catherine L.; Forbes, Andrew B.; Tonkin, Andrew; Berezovskaya, Sofia; Tan, Lynn; Ding, Changhai; Wang, Yuanyuan (Frontiers in Medicine, 2022)
Objective: Populations with knee osteoarthritis (KOA) are at increased risk of cardiovascular disease, due to higher prevalence of risk factors including dyslipidemia, where statins are commonly prescribed. However, the effect of statins on muscles and symptoms in this population is unknown. Thus, this study examined the effect of atorvastatin on muscle properties in patients with symptomatic KOA. Design: Post-hoc analysis of a two-year multicentre randomised, double-blind, placebo-controlled trial. Setting: Australian community Participants: Participants aged 40-70 years (mean age 55.7 years, 55.6% female) with KOA who met the American College of Rheumatology clinical criteria received atorvastatin 40mg daily (n=151) or placebo (n=153). Main outcome measures: Levels of creatinine kinase (CK), aspartate transaminase (AST) and alanine transaminase (ALT) at 1, 6, 12 and 24 months; muscle strength (by dynamometry) at 12 and 24 months; vastus medialis cross-sectional area (CSA) on magnetic resonance imaging at 24 months; and self-reported myalgia. Results: There were no significant between-group differences in CK and AST at all timepoints. The atorvastatin group had higher ALT than placebo group at 1 (median 26 vs 21, p=0.004) and 6 (25 vs 22, p=0.007) months without significant between-group differences at 12 and 24 months. Muscle strength increased in both groups at 24 months without between-group differences [mean 8.2 (95%CI 3.5, 12.9) vs 5.9 (1.3, 10.4), p=0.49]. Change in vastus medialis CSA at 24 months favoured the atorvastatin group [0.11 (-0.10, 0.31) vs -0.23 (-0.43, -0.03), p=0.02] but of uncertain clinical significance. There was a trend for more myalgia in the atorvastatin group (8/151 vs 2/153, p=0.06) over 2 years, mostly occurring within 6 months (7/151 vs 1/153, p=0.04). Conclusions: In those with symptomatic KOA, despite a trend for more myalgia, there was no clear evidence of an adverse effect of atorvastatin on muscles, including those most relevant to knee joint health.